2018
DOI: 10.3390/ijms19103176
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and the Kidney in the Space Environment

Abstract: In space, the special conditions of hypogravity and exposure to cosmic radiation have substantial differences compared to terrestrial circumstances, and a multidimensional impact on the human body and human organ functions. Cosmic radiation provokes cellular and gene damage, and the generation of reactive oxygen species (ROS), leading to a dysregulation in the oxidants–antioxidants balance, and to the inflammatory response. Other practical factors contributing to these dysregulations in space environment inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 106 publications
(125 reference statements)
0
26
0
Order By: Relevance
“…As is known, elevated ROS levels can disrupt lipids, proteins, and DNA, resulting in the membrane damage and eventual cell death [ 139 ]. Oxidative stress is therefore linked to a wide range of pathological anomalies and degenerative diseases, especially erythrocytes and brain cells that involve oxygen transport and aerobic respiration [ 140 , 141 , 142 , 143 , 144 , 145 ]. Table 2 presents a list of in vivo studies summarizing the different administration routes of GO-based nanomaterials and their associated biological effects.…”
Section: Cell Viability and Toxicitymentioning
confidence: 99%
“…As is known, elevated ROS levels can disrupt lipids, proteins, and DNA, resulting in the membrane damage and eventual cell death [ 139 ]. Oxidative stress is therefore linked to a wide range of pathological anomalies and degenerative diseases, especially erythrocytes and brain cells that involve oxygen transport and aerobic respiration [ 140 , 141 , 142 , 143 , 144 , 145 ]. Table 2 presents a list of in vivo studies summarizing the different administration routes of GO-based nanomaterials and their associated biological effects.…”
Section: Cell Viability and Toxicitymentioning
confidence: 99%
“…The mechanical unloading of cells under microgravity conditions shifts the balance between physiology and pathophysiology, accelerating the progression and development of some disease states. For example, kidney stone formation is accelerated under microgravity conditions compared to Earth's gravity (1 g) (Pavlakou et al, 2018). Similarly, osteoporosis can take decades to develop under normal gravitational loading, yet this disease can be modeled under microgravity over shorter time scales (Pajevic et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The inherent environment during spaceflight, such as microgravity, cosmic radiation, and hypomagnetic field, could induce injury or physical and physiological stress and cause a cumulative impact on the body (Garrett-Bakelman et al, 2019). Growing investigations have clearly demonstrated that microgravity may affect the oxidative stress response not only in hosts but also in a variety of bacteria (Jayroe et al, 2012; Aunins et al, 2018; Pavlakou et al, 2018). The related oxidative stress is involved in the progression of physiological alterations, such as immune dysfunction, inflammation, muscle atrophy, bone loss, and metabolism disorder (Lawler et al, 2003; Jackson, 2009; Wauquier et al, 2009; Bergouignan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was found that simulated weightlessness remarkably decreased the amount of sinapinic acid, 4-hydroxypyridine and indolelactate, which suggested the high oxidative status and oxidative stress within the intestinal tract that might contribute to the inflammation and breakdowns of intestinal homeostasis. Some literature has reported oxidative bursts under space environments and simulated microgravity or weightlessness conditions (Yamauchi et al, 2002; Jayroe et al, 2012; Seawright et al, 2017; Pavlakou et al, 2018). Mechanisms of interactions between intestinal microbiota metabolites and oxidative stress-induced intestinal dysfunction under microgravity need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%